2017
DOI: 10.1159/000464460
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Activation of Smoothened in the Renal Collecting Ducts Leads to Renal Hypoplasia, Hydronephrosis, and Hydroureter

Abstract: Sonic Hedgehog (Shh) signaling plays a major role in and is essential for regulation, patterning, and proliferation during renal development. Smoothened (Smo) plays a pivot role in transducing the Shh-glioma-associated oncogene Kruppel family member. However, the cellular and molecular mechanism underlying the role of sustained Smo activation in postnatal kidney development is still not clearly understood. Using a conditional knockin mouse model that expresses a constitutively activated form of Smo (SmoM2) upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Expression of Smo-M2 alone during postnatal development using Pkhd1 Cre did not generate cysts (data not shown), consistent with a previous report. 39 Concomitant expression of Smo-M2 and inactivation of Pkd1 in the early postnatal collecting duct did not alter the kidney cystic phenotype compared with Pkd1 deletion alone ( Figure 2, A and B). We also tested whether ligandindependent activation of the Hedgehog pathway could influence polycystic disease in the slower-progressing adult-onset ADPKD model.…”
Section: Activation Of Hedgehog Pathway In Renal Epithelial Cells Doementioning
confidence: 90%
“…Expression of Smo-M2 alone during postnatal development using Pkhd1 Cre did not generate cysts (data not shown), consistent with a previous report. 39 Concomitant expression of Smo-M2 and inactivation of Pkd1 in the early postnatal collecting duct did not alter the kidney cystic phenotype compared with Pkd1 deletion alone ( Figure 2, A and B). We also tested whether ligandindependent activation of the Hedgehog pathway could influence polycystic disease in the slower-progressing adult-onset ADPKD model.…”
Section: Activation Of Hedgehog Pathway In Renal Epithelial Cells Doementioning
confidence: 90%
“…Recent research has focused on the Ptch structure (8,11), but it had still not proved that the expression of Ptch (P1 and P2) is abnormal in UPJO. Gupta et al found that the expression of P1 in hydronephrotic mice model was high compared to normal (10). His research was based on arti cial mutant mice, not on real UPJO patients.…”
Section: Discussionmentioning
confidence: 99%
“…Despite various investigations, the Ptch regulation in UPJO children remains unclear, and whether there is variation is yet to be proved (9). The expression of P1 and P2 have been compared in hydronephrotic models and contiguous segments in the same patients' ureters in previous studies, but the same parts of human ureteropelvic junction segments have not been compared (5,10).…”
Section: Introductionmentioning
confidence: 99%
“…The germline loss of Smo results in embryonic lethality prior to metanephric kidney development. Smo deletion from the ureteric epithelium does not cause detectable phenotypes (Cain et al, 2009) although expression of constitutively active Smo in the ureteric epithelium leads to renal hypoplasia and hydronephrosis (Gupta et al, 2017).…”
Section: Discussionmentioning
confidence: 99%